Impacto ambiental por productos quimicos usados en la produccion camaronera las palmas - Narvaez Cajo, Nestor Nelson (Machala : Universidad Técnica de Machala, 2024)
Aquaculture is an activity of main economic benefit for Ecuador, occupying large hectares of the coastal zone. Its development process is accompanied by different actions/activities which entail a condition or intervention towards the environment and its resources. The purpose of this study is to evaluate the environmental impact produced by the activities of the shrimp company “Las Palmas” in the canton of El Guabo, through the collection of secondary information and assessment of the state of the environmental components through the Leopold matrix. to establish strategies to mitigate the negative effects observed. The research was carried out in the period 2023-2024 in the Barbones parish, a site belonging to the El Guabo canton - province of El Oro. A qualitative methodology was used based on the researcher's subjective assessment of the environmental impacts observed in the study area. being that, according to the results found, it is established that the operations in the drainage, feeding and fertilization processes have an impact on the environmental factors in the area, particularly the changes and effects on the quality of the water, wetlands, vegetation and aquatic life. According to what was observed, the company presents inadequate management of its operations, causing the impact on the environmental components of the area where it is developed, therefore, the incorporation and compliance of an environmental management plan (EMP) is considered a point fundamental for the improvement of the internal management of the company. Therefore, within the proposal, an EMP is developed aimed at mitigating the effects of the negative impacts generated in the “Las Palmas” shrimp farm, through the implementation of measures that allow preventing and reducing the environmental impacts found. The proposal presents all eight plans: Impact prevention and mitigation plan, Non-hazardous waste management plan, Hazardous waste management plan, Training plan, Community relations plan, Industrial safety and occupational health plan, Plan prevention, risk and contingency control, Monitoring, follow-up and evaluation plan, and Abandonment or closure plan. The proposal presents a validation of positive feasibility, counting on technical knowledge, financial solvency, and socio-environmental benefits towards the study area. Considering the above, it is concluded that the company presents inadequate management in its operations, highlighting: generation of noise and suspended particles due to the use of pumps, machinery and vehicles; loss of vegetation cover and soil alteration by plowing, harrowing and walling of pools; wastewater discharges into nearby bodies of water due to water exchange in swimming pools with the presence of chemical waste, among others. Therefore, the implementation of a PMA focused on preventing, reducing and mitigating the effects produced by the development of shrimp activity in the sector is recommended, providing environmental and social security for the environment, workers and nearby communities that make use of the resources. resources. Finally, compliance with the points established within the PMA is recommended, guaranteeing the monitoring of activities and their application deadlines. avoiding further environmental degradation in production sectors.
La acuicultura es una actividad de principal beneficio económico para el Ecuador, ocupando grandes hectáreas de la zona costera. Su proceso de desarrollo está acompañado de diferentes acciones/actividades las cuales conllevan una afección o intervención hacia el medio y sus recursos. El presente estudio tiene como finalidad Evaluar el impacto ambiental producido por las actividades de la empresa camaronera “Las Palmas” en el cantón El Guabo, mediante la recopilación de información secundaria y valoración del estado de los componentes ambientales a través de la matriz de Leopold, para establecer estrategias que permitan mitigar los efectos negativos observados. La investigación se realizó en el período 2023-2024 en la parroquia Barbones, sitio perteneciente al cantón El Guabo – provincia de El Oro. Se empleó una metodología cualitativa basada en la valoración subjetiva del investigador sobre los impactos ambientales observados en el área de estudio, siendo que, acorde a los resultados encontrados se establece que las operaciones en los procesos de drenaje, alimentación y fertilización presentan una afectación a los factores ambientales en la zona, particularmente los cambios y efectos sobre la calidad del agua, los humedales, la vegetación y la vida acuática. De acuerdo con lo observado, la empresa presenta un manejo inadecuado de sus operaciones, ocasionando la afectación en los componentes ambientales del área en donde se desarrolla, por tanto, la incorporación y cumplimiento de un plan de manejo ambiental (PMA) se considera un punto fundamental para el mejoramiento de la gestión interna de la empresa. Por tanto, dentro de la propuesta se desarrolla un PMA destinado a mitigar los efectos de los impactos negativos que se generan en la camaronera “Las Palmas”, mediante la implementación de medidas que permitan prevenir y reducir los impactos ambientales encontrados. La propuesta presenta la totalidad de ocho planes: Plan de prevención y mitigación de impacto, Plan de manejo de desecho no peligroso, Plan de manejo de desecho peligroso, Plan de capacitación, Plan de relaciones comunitarias, Plan de seguridad industrial y salud ocupacional, Plan de prevención, control de riesgo y contingencia, Plan de monitoreo, seguimiento y evaluación, y Plan de abandono o cierre. La propuesta presenta una validación de factibilidad positiva, contando con los conocimientos técnicos, solvencia financiera, y beneficios socio-ambientales hacia el área de estudio. Considerando lo expuesto se concluye que, la empresa presenta un manejo inadecuado en sus operaciones, destacando: generación de ruido y partículas en suspensión por uso de bombas, maquinarias y vehículos; pérdida de cobertura vegetal y alteración del suelo por arado, rastrado y amurallamiento de piscinas; vertidos de aguas residuales a cuerpos de agua cercanos por recambio de agua en piscinas con presencia de residuos químicos, entre otros. Por tanto, se recomienda la implementación de un PMA centrado en prevenir, reducir y mitigar los efectos que produce el desarrollo de la actividad camaronera en el sector, brindando una seguridad ambiental y social sobre el medio, trabajadores y comunidades cercanas que hagan uso de los recursos. Finalmente se recomienda el cumplimiento de los puntos establecidos dentro del PMA, garantizando el seguimiento de las actividades y sus plazos de aplicación. evitando mayores degradaciones ambientales en los sectores de producción.
Keywords: CAMARONERA; IMPACTO; AMBIENTE; PLAN DE MANEJO